Cost-effectiveness analysis of COVID-19 case quarantine strategies in two australian states: New South Wales and Western Australia - Adrian Melia; Doowon Lee; Nader Mahmoudi; Yameng Li; Francesco Paolucci (Journal of Risk and Financial Management, 2021)
Two main strategies, home and hotel isolation, have been used to isolate COVID-19 cases in most countries. Both have proven to be somewhat medically effective, but the costs to produce the desired outcome remain unclear. We used a decision tree model to compare alternatives and a simulation model to determine the household structure and provide recommendations for the most cost-effective way to isolate a COVID-19 patient in two Australian States, New South Wales (NSW) and Western Australia (WA). The results show that although the average cost of isolating a confirmed case at home is lower than that of a hotel quarantine, it is demonstrable that the decision depends on household size and the ages of household members. If the household members' ages are old or the household size is large, the expected mean cost of home quarantine might be higher than hotel quarantine. Our study, therefore, provides the government with a cost-effective insight into making quarantine policies.
Keywords: 330; Australian states; cost-effective options; COVID-19 pandemic; decision tree model; home quarantine; hotel quarantine; self-isolation